Apakah Remaja Panti Asuhan Merasa Kesepian? Menilik Pengaruh Interaksi Sosial Dan Self-Compassion - Asep Saepuloh; Cempaka Putrie Dimala; Anggun Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Loneliness is a psychological problem often experienced by adolescents in orphanages, due to limited social relationships and emotional support. This study aims to determine the effect of social interaction and self-compassion on loneliness among adolescents living in orphanages in Karawang Regency. Using a quantitative approach and a causal design, this study involved 103 adolescents aged 13–19 years residing in six orphanages in the region, selected through a saturated sampling technique. The research instruments included a loneliness scale based on the UCLA Loneliness Scale, a social interaction scale developed based on Sarwono's concept of social interaction, and the Self-Compassion Scale (SCS). Regression analysis results indicate that social interaction (β = -0.849; p < 0.05) and self-compassion (β = -0.288; p < 0.05) partially have a significant negative effect on loneliness. Simultaneously, both also had a significant effect on loneliness (F = 55.816; p < 0.05), contributing 52.7% to the variation in loneliness, with social interaction contributing 32.15% and self-compassion 20.58%. These results indicate that improving the quality of social interaction and the ability to positively accept oneself can help reduce loneliness levels among orphanage adolescents.